The Development Of Ombudsman - Yardley, Sir David (Journal of Malaysian and Comparative Law, 2001)
In the 1997 number of the Commermorative Issue of The Journal of Malaysian and Comparative Law, I published an article entitled 'Ombudsmen in the United Kingdom', in which I endeavoured to set out the general principles of government accountability in the UK, and to stress the ways in which in recent years there had been increased encouragement and provision for methods of pursuing grievances which are alternative to the court process.